Preparation method of platinum-doped modified cobalt-based catalyst
The preparation of platinum-doped modified cobalt-based catalysts through one-step annealing method solves the problems of scarce reserves and high cost of precious metal-based catalysts, and achieves the dual advantages of high catalytic performance and cost-effectiveness.
Patent Information
- Application Number
- CN202310026643.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-01-09
AI Technical Summary
The existing precious metal-based catalysts have scarce reserves and high costs, which are not suitable for large-scale promotion and application. The catalyticity of transition metal-nitrogen-carbon materials is still inferior to that of platinum-based catalysts.
A platinum-doped modified cobalt-based catalyst was prepared by one-step annealing method. By immersing the basic cobalt salt substrate material coated with dopamine polymer in a chloroplatinic acid solution and annealing under argon protection, a platinum-doped nitrogen-doped carbon structure was formed.
The high catalytic performance of the catalyst is achieved, which is better than or less than that of the platinum-based catalyst. At the same time, due to the small amount of platinum doping, the cost of the catalyst is also effectively controlled.
Smart Images

Figure CN116099566B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of an electrocatalyst with high catalytic performance, which is applied to the field of green energy storage and conversion devices represented by fuel cells, water electrolysis devices and rechargeable metal-based batteries. Background Art
[0002] The continuous consumption of fossil fuels such as petroleum and coal has promoted the development of efficient energy storage and conversion technologies. Rechargeable metal-air batteries, water electrolysis devices and fuel cells have attracted attention due to their inherent environmental friendliness, high energy density and safety of energy conversion. Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are two important reactions in water electrolysis; oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are considered to be two key processes in rechargeable metal-air batteries. These electrochemical reactions are kinetically slow and usually require overcoming a large overpotential to proceed. In order to accelerate the reaction process, people are committed to exploring electrocatalysts with high catalytic activity. Nowadays, the widely used catalysts are mainly precious metal-based catalysts, but precious metal-based catalysts are scarce in reserves and expensive, and are not suitable for large-scale promotion and application. Therefore, developing non-precious metal-based catalysts to reduce or replace the use of precious metal-based catalysts is an effective way to solve the current problem.
[0003] In recent years, transition metal-nitrogen-carbon (TM-NC) materials have been widely reported in OER and ORR, and they are considered to be the most promising cathode materials for rechargeable metal-air batteries. Generally speaking, the electrocatalytic activity of transition metals in alkaline media for ORR is Fe>Co>Ni, while their electrocatalytic activity for OER is Ni>Co>Fe. Obviously, Co-NC materials are very promising bifunctional catalysts, which is also due to their moderate adsorption-dissolution free energy for ORR and OER intermediates. In addition, the electronic structure of metal cobalt (Co) is closest to that of precious metal platinum (Pt), making it an ideal substitute for platinum-based catalysts. However, the catalytic performance of Co-NC catalytic materials is still inferior to that of platinum-based catalysts. If a small amount of Pt can be doped into Co-NC catalytic materials, can the catalyst have a catalytic performance that is better than or not inferior to that of platinum-based catalytic materials? And because the amount of Pt doped is small, the cost of the catalyst can also be effectively controlled. This method has great research significance and practical value in promoting the large-scale commercial application of electrocatalytic materials.
[0004] As a nitrogen-doped carbon (NC) substrate material supporting transition metals, carbon nanotubes (NCNTs) have the characteristics of large specific surface area, high conductivity, porosity, corrosion resistance and easy chemical modification by introducing metal sites, and are considered to be an ideal carrier for giving electrocatalysts high activity and durability. If Co@NCNTs is used as a substrate material and doped with a small amount of precious metal Pt to obtain a platinum-doped cobalt-based catalytic material, it will definitely have high catalytic potential. Summary of the invention
[0005] In view of this, the present invention provides a method for obtaining a platinum-doped modified cobalt-based catalyst by one-step annealing, wherein the preparation method comprises the following steps:
[0006] A method for preparing a platinum-doped modified cobalt-based catalyst, the preparation method comprising:
[0007] S1. Immersing a basic cobalt salt substrate material coated with a dopamine polymer in a chloroplatinic acid solution to obtain a substrate material having a platinum-doped basic cobalt salt precursor with a surface layer coated with a polydopamine polymer;
[0008] S2. Place the substrate material obtained in S1 in a tube furnace, add dicyandiamide, and anneal under argon protection to obtain a platinum-doped modified cobalt-based catalyst.
[0009] The preparation method of the basic cobalt salt substrate material coated with dopamine polymer is as follows: cobalt chloride and urea are dissolved in deionized water, and a needle-shaped basic cobalt salt array is grown on a conductive substrate by a chemical bath deposition method to obtain a substrate material with basic cobalt salt grown thereon;
[0010] The substrate material with the basic cobalt salt grown thereon is soaked in a dopamine solution for a certain period of time, then taken out, its surface is rinsed with deionized water and dried, so that a uniform layer of dopamine polymer is coated on the surface of the basic cobalt salt.
[0011] The loading amount of basic cobalt salt on the substrate material is 0.5-2 mg / cm 2 .
[0012] The concentration of dopamine hydrochloride is 0.1-0.4 mg / L, and the substrate material is immersed in the dopamine hydrochloride buffer solution for 12-24 hours.
[0013] The molar ratio of platinum ions in the chloroplatinic acid solution to cobalt ions in the basic cobalt salt (Co(OH)2) supported by the substrate material is 3:100 to 10:100.
[0014] The cobalt-platinum ion replacement temperature is 30-80°C, and the replacement time is 12-24h.
[0015] The annealing temperature is 700-900°C and the annealing time is 2-3h.
[0016] The first step is to grow basic cobalt salt on the substrate material: first, dissolve a certain amount of cobalt chloride hexahydrate and urea in deionized water, and stir magnetically to obtain a uniform solution; then pour the solution into a glass test tube and put the substrate material into the solution so that the solution submerges the substrate material; this is to allow the substrate material to fully contact the solution, and the basic cobalt salt can grow evenly on the substrate material. Then put the test tube into a constant temperature oven for hydrothermal reaction for a certain period of time, cool it down, take it out, rinse the substrate material with water and dry it, and obtain the basic cobalt salt grown in situ on the substrate material. The purpose of this step is to allow the basic cobalt salt to grow evenly on the substrate.
[0017] The second step is the coating of dopamine polymer: dopamine hydrochloride is dissolved in a weak alkaline buffer solution with a pH value of about 7.5-8.5 to prepare a dopamine hydrochloride buffer solution of a certain concentration, the substrate material grown with basic cobalt salt is soaked in the dopamine solution for a certain period of time and then taken out, the surface is rinsed with deionized water and dried, that is, a uniform layer of dopamine polymer is coated on the surface of the basic cobalt salt. In this process, the pH value of the buffer solution for dissolving dopamine hydrochloride is about 7.5-8.5, because dopamine hydrochloride dissolved in pure water will make the solution acidic, and the acidic solution will dissolve the basic cobalt salt. Therefore, a weak alkaline buffer must be used to dissolve and neutralize dopamine hydrochloride. Only in a neutral or weakly alkaline environment can the basic cobalt salt exist stably. The effect of coating a layer of dopamine polymer is equivalent to coating a layer of film on the outer layer of the basic cobalt salt, which can make it grow stably on the substrate fiber without falling off. In addition, the polymer can provide a nitrogen source in the subsequent annealing step to form a nitrogen-doped carbon structure.
[0018] The third step is doping with platinum ions: immerse the base material obtained by the above steps in a chloroplatinic acid solution, react at a certain temperature for a certain time, so that the platinum ions and cobalt ions are fully replaced, and finally a base material with a platinum-doped basic cobalt salt precursor with a surface coated with polydopamine polymer is obtained. Most platinum-doped catalytic materials are doped with platinum after annealing, but the present invention is to dope platinum before annealing, and obtain the catalytic material by one-step annealing. The preparation process of the present invention is simpler, and the distribution of platinum atoms can be more uniform during the Co / Pt co-annealing process, and it is possible to form more single-atom platinum catalytic active sites, which is very beneficial to the catalytic performance of the catalyst.
[0019] The fourth step is annealing of the precursor: the Pt-doped basic cobalt salt precursor with dopamine polymer wrapped on the surface of the substrate material is placed in the center of the tubular furnace, a certain amount of dicyandiamide is taken and placed upstream of the tubular furnace, annealed at a certain temperature for a certain time under argon protection, and the platinum-doped modified cobalt-based catalytic material is obtained after cooling and taking out. In this process, the annealing must be carried out under argon protection throughout the process. The high annealing temperature makes the entry of a trace amount of air affect the normal progress of the reaction. The annealing temperature and annealing time are the key to the catalyst obtaining high catalytic performance, and a large number of experiments to obtain the optimal solution are also one of the key points of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 ORR polarization curves of the samples prepared in Example 1, Example 2, Example 3 and Example 4 measured in oxygen-saturated (a) alkaline, (b) neutral, and (c) acidic electrolytes.
[0021] Figure 2 HER polarization curves of the samples prepared in Example 1, Example 2, Example 3 and Example 4 measured in nitrogen-saturated (a) alkaline, (b) neutral, and (c) acidic electrolytes.
[0022] Figure 3 HOR polarization curves of the samples prepared in Example 1, Example 2, Example 3 and Example 4 measured in an alkaline electrolyte saturated with hydrogen.
[0023] Figure 4 HER polarization curve of the sample prepared in Example 5 measured in a nitrogen-saturated alkaline electrolyte.
[0024] Figure 5 HER polarization curve of the sample prepared in Example 6 measured in a nitrogen-saturated alkaline electrolyte.
[0025] Figure 6 The XRD patterns of the samples prepared in Example 1, Example 3 and Example 4 are shown.
[0026] Figure 7 This is the SEM image of the sample prepared in Example 1.
[0027] Figure 8 This is the SEM image of the sample prepared in Example 3.
[0028] Fig. 9 This is the SEM image of the sample prepared in Example 4. DETAILED DESCRIPTION
[0029] Characterization conditions:
[0030] All electrochemical tests in the present invention were performed by Shanghai Chenhua Instrument Co., Ltd. CHI760E electrochemical workstation with CHI760E software. A graphite electrode was used as an auxiliary electrode, a replaceable platinum electrode clip and a test sample were used as working electrodes, and a mercury / mercuric oxide electrode (alkaline environment), a silver / silver chloride electrode (neutral environment) or a mercury / mercurous sulfate electrode (acidic environment) was used as a reference electrode to assemble a standard three-electrode device for testing.
[0031] ORR performance test: The alkaline ORR tests of the embodiments of the present invention were all carried out in an oxygen-saturated 0.1 M potassium hydroxide solution; the neutral ORR tests were all carried out in an oxygen-saturated mixed solution of dipotassium hydrogen phosphate and potassium dihydrogen phosphate (pH = 7); the acidic ORR tests were all carried out in an oxygen-saturated 0.05 M sulfuric acid solution.
[0032] HER performance test: The alkaline HER tests of the embodiments of the present invention were all carried out in a 1 M potassium hydroxide solution saturated with nitrogen; the neutral HER tests were all carried out in a mixed solution of dipotassium hydrogen phosphate and potassium dihydrogen phosphate (pH = 7) saturated with nitrogen; the acidic HER tests were all carried out in a 0.05 M sulfuric acid solution saturated with nitrogen.
[0033] HOR performance test: The alkaline HOR tests of the embodiments of the present invention were all carried out in a 0.1 M potassium hydroxide solution saturated with hydrogen.
[0034] Made by Rigaku of Japan The XRD test of the embodiment of the present invention was performed using an Ultima IV X-ray diffractometer. The TEM test of the embodiment of the present invention was performed using a FEI Quanta 250 scanning electron microscope produced by Rigaku Corporation of Japan.
[0035] Example 1
[0036] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2 ) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2 ) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm 2). Take 20 mg of dopamine hydrochloride and dissolve it in 100 mL of buffer solution with pH = 8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100 r / min, react at room temperature for 24 hours, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Place the carbon paper treated as above in the center of the tubular furnace, take 1 g of dicyandiamide and place it upstream of the tubular furnace, and under argon protection, heat from room temperature to 350°C at 10°C / min, react at constant temperature for 1 hour, then heat to 900°C at 3°C / min, and react at constant temperature for 2 hours to obtain the final sample.
[0037] Figure 1 The ac and Table 1 show the ORR catalytic performance of the sample of Example 1 in different electrolytes, and its half-wave potential (E 1 / 2 ) is 0.89V, E 1 / 2 =0.82, E in acidic electrolyte 1 / 2 =0.78V. Figure 2 The ac and Table 2 show the HER catalytic performance of the sample of Example 1 in different electrolytes, which achieves 10 mA cm in alkaline electrolyte. 2 The overpotential required for the current density is 167 mV, and 10 mA cm-2 is achieved in a neutral electrolyte. 2 The overpotential required for the current density is 135 mV, and 10 mA cm is achieved in acidic electrolyte. 2 The overpotential required for the current density is 14 mV. Figure 3 ac and Table 3 show the HOR catalytic performance of the sample of Example 1 in alkaline electrolyte, and its HOR half-wave potential is 18 mV. Figure 6 and Figure 7 The XRD and SEM images of the sample are shown.
[0038] Example 2
[0039] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2 ) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2 ) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm2 ). Take 20mg of dopamine hydrochloride and dissolve it in 100mL of buffer solution with pH=8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100r / min, react at room temperature for 24h, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Take 3mL of methanol and DMF with a volume ratio of 1:1, add 265uL of 1mol / L chloroplatinic acid isopropanol solution and mix evenly (the molar ratio of cobalt to platinum is 100:3). Spread the above carbon paper flat in a glass culture dish, pour in the mixed solution and make it submerge the carbon paper, seal it, and place it in a constant temperature box at 60℃ to react for 24h. After cooling, take it out, wash it with deionized water and dry it. Place the carbon paper treated as above in the center of the tube furnace, take 1g of dicyandiamide and place it upstream of the tube furnace, and under argon protection, heat from room temperature to 350℃ at a rate of 10℃ / min, react at this temperature for 1h, then heat to 900℃ at a rate of 3℃ / min, react at this temperature for 2h to obtain the final sample.
[0040] Figure 1 The ac and Table 1 show the ORR catalytic performance of the sample of Example 2 in alkaline electrolyte, and its half-wave potential (E 1 / 2 ) is 0.91V. Figure 2 The ac and Table 2 show the HER catalytic performance of the sample of Example 2 in alkaline electrolyte, which achieves 10 mA cm 2 The overpotential required for the current density is 167 mV, and 10 mA cm-2 is achieved in a neutral electrolyte. 2 The overpotential required for the current density is 180 mV. Figure 3 ac in and Table 3 show the HOR catalytic performance of the sample of Example 2 in alkaline electrolyte, and its HOR half-wave potential is 7 mV.
[0041] Example 3
[0042] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2 ) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2 ) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm 2). Take 20mg of dopamine hydrochloride and dissolve it in 100mL of buffer solution with pH=8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100r / min, react at room temperature for 24h, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Take 3mL of methanol and DMF with a volume ratio of 1:1, add 440uL of 1mol / L chloroplatinic acid isopropanol solution and mix evenly (the molar ratio of cobalt to platinum is 100:5). Spread the above carbon paper flat in a glass culture dish, pour in the mixed solution and make it submerge the carbon paper, seal it, and place it in a constant temperature box at 60℃ to react for 24h. After cooling, take it out, wash it with deionized water and dry it. Place the carbon paper treated as above in the center of the tube furnace, take 1g of dicyandiamide and place it upstream of the tube furnace, and under argon protection, heat from room temperature to 350℃ at a rate of 10℃ / min, react at this temperature for 1h, then heat to 900℃ at a rate of 3℃ / min, react at this temperature for 2h to obtain the final sample.
[0043] Figure 1 The ac and Table 1 show the ORR catalytic performance of the sample of Example 3 in different electrolytes, and its half-wave potential (E 1 / 2 ) is 0.92V, E 1 / 2 =0.89, E in acidic electrolyte 1 / 2 =0.86V. Figure 2 The ac and Table 2 show the HER catalytic performance of the sample of Example 3 in different electrolytes, which achieves 10 mA cm in alkaline electrolyte. 2 The overpotential required for the current density is 131 mV, and 10 mA cm is achieved in a neutral electrolyte. 2 The overpotential required for the current density is 126 mV, and 10 mA cm is achieved in acidic electrolyte. 2 The overpotential required for the current density is 1 mV. Figure 3 ac and Table 3 show the HOR catalytic performance of the sample of Example 3 in alkaline electrolyte, and its HOR half-wave potential is 6 mV. Figure 6 and Figure 8 The XRD and SEM images of the sample are shown. Table 4 is a table of element contents of the sample of Example 3, from which it can be seen that the atomic ratio of platinum to cobalt is less than 5:100.
[0044] Example 4
[0045] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2 ) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm 2 ). Take 20mg of dopamine hydrochloride and dissolve it in 100mL of buffer solution with pH=8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100r / min, react at room temperature for 24h, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Take 3mL of methanol and DMF with a volume ratio of 1:1, add 880uL of 1mol / L chloroplatinic acid isopropanol solution and mix evenly (the molar ratio of cobalt to platinum is 100:10). Spread the above carbon paper flat in a glass culture dish, pour in the mixed solution and make it submerge the carbon paper, seal it, and place it in a constant temperature box at 60℃ to react for 24h. After cooling, take it out, wash it with deionized water and dry it. Place the carbon paper treated as above in the center of the tube furnace, take 1g of dicyandiamide and place it upstream of the tube furnace, and under argon protection, heat from room temperature to 350℃ at a rate of 10℃ / min, react at this temperature for 1h, then heat to 900℃ at a rate of 3℃ / min, react at this temperature for 2h to obtain the final sample.
[0046] Figure 1 The ac and Table 1 show the ORR catalytic performance of the sample of Example 4 in different electrolytes, and its half-wave potential (E 1 / 2 ) is 0.92V, E 1 / 2 =0.89, E in acidic electrolyte 1 / 2 =0.85V. Figure 2 The ac and Table 2 show the HER catalytic performance of the sample of Example 4 in different electrolytes, which achieves 10 mA cm in alkaline electrolyte. 2 The overpotential required for the current density is 116 mV, and 10 mA cm is achieved in a neutral electrolyte. 2 The overpotential required for the current density is 126 mV, and 10 mA cm is achieved in acidic electrolyte. 2 The overpotential required for the current density is 4 mV. Figure 3 ac and Table 3 show the HOR catalytic performance of the sample of Example 4 in alkaline electrolyte, and its HOR half-wave potential is 6 mV. Figure 6 and Fig. 9 The XRD and SEM images of the sample are shown.
[0047] Example 5
[0048] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2 ) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2 ) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm 2 ). Take 20mg of dopamine hydrochloride and dissolve it in 100mL of buffer solution with pH=8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100r / min, react at room temperature for 24h, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Take 3mL of methanol and DMF with a volume ratio of 1:1, add 440uL of 1mol / L chloroplatinic acid isopropanol solution and mix evenly (the molar ratio of cobalt to platinum is 100:5). Spread the above carbon paper flat in a glass culture dish, pour in the mixed solution and make it submerge the carbon paper, seal it, and place it in a constant temperature box at 60℃ to react for 24h. After cooling, take it out, wash it with deionized water and dry it. Place the carbon paper treated as above in the center of the tube furnace, take 1g of dicyandiamide and place it upstream of the tube furnace, and under argon protection, heat from room temperature to 350℃ at a rate of 10℃ / min, react at this temperature for 1h, then heat to 700℃ at a rate of 3℃ / min, react at this temperature for 2h to obtain the final sample.
[0049] Figure 4 The HER polarization curve of the sample of Example 5 measured in alkaline electrolyte is 10 mA cm 2 The overpotential required for the current density is 66 mV.
[0050] Example 6
[0051] Take 1.428g of cobalt chloride hexahydrate and 2.667g of urea and dissolve them in 40mL of deionized water to obtain a hydrothermal reagent with a metal ion concentration of 0.15mol / L. Take an area of 10cm 2 (2.5×5cm 2 ) was rinsed with anhydrous ethanol, placed in a mixture of water and alcohol for 15 minutes, then taken out and cleaned with deionized water. 2) were transferred to glass test tubes and then transferred to a water heating box for heat treatment at 90°C for 2h. After cooling to room temperature, the carbon paper surface was rinsed with deionized water and dried to obtain a pale pink basic cobalt salt precursor sample (the loading amount of basic cobalt salt on carbon paper was 1mg / cm 2 ). Take 20mg of dopamine hydrochloride and dissolve it in 100mL of buffer solution with pH=8.5. Hang the carbon paper with basic cobalt salt prepared above in the dopamine solution so that the carbon paper is completely immersed in the solution. Set the speed to 100r / min, react at room temperature for 24h, and after the reaction is completed, use deionized water to wash the carbon paper and dry it. Take 3mL of methanol and DMF with a volume ratio of 1:1, add 440uL of 1mol / L chloroplatinic acid isopropanol solution and mix evenly (the molar ratio of cobalt to platinum is 100:5). Spread the above carbon paper flat in a glass culture dish, pour in the mixed solution and make it submerge the carbon paper, seal it, and place it in a constant temperature box at 60℃ to react for 24h. After cooling, take it out, wash it with deionized water and dry it. Place the carbon paper treated as above in the center of the tube furnace, take 1g of dicyandiamide and place it upstream of the tube furnace, and under argon protection, heat from room temperature to 350°C at a rate of 10°C / min, react at this temperature for 1h, then heat to 800°C at a rate of 3°C / min, and react at this temperature for 2h to obtain the final sample.
[0052] Figure 5 The HER polarization curve of the sample of Example 6 measured in alkaline electrolyte achieves 10 mA cm 2 The overpotential required for the current density is 60 mV.
[0053] Table 1: Comparison of ORR catalytic performance data of different example samples in alkaline, neutral and acidic systems
[0054]
[0055] Table 2: Comparison of HER catalytic performance data of different example samples in alkaline, neutral and acidic systems
[0056]
[0057]
[0058] Table 3: Comparison of HOR catalytic performance data of different examples in alkaline system
[0059]
[0060] Table 4: Element content of samples in Example 3
[0061]
Claims
1. A method for preparing a platinum-doped modified cobalt-based catalyst, characterized in that: The preparation method is: S1. Immersing a basic cobalt salt substrate material coated with a dopamine polymer in a chloroplatinic acid solution to obtain a substrate material having a platinum-doped basic cobalt salt precursor with a surface layer coated with a polydopamine polymer, wherein the molar ratio of platinum ions in the chloroplatinic acid solution to cobalt ions in the basic cobalt salt Co(OH)2 loaded on the substrate material is 5:100 or 10:100, the cobalt-platinum ion replacement temperature is 30-80°C, the replacement time is 12-24 h, and the loading amount of the basic cobalt salt on the substrate material is 0.5-2 mg / cm 2 ; S2. Place the substrate material obtained in S1 in a tube furnace, add dicyandiamide, and anneal under argon protection to obtain a platinum-doped modified cobalt-based catalyst. The annealing temperature is 700 to 900° C. and the annealing time is 2 to 3 h.
2. The method for preparing a platinum-doped modified cobalt-based catalyst according to claim 1, characterized in that: The preparation method of the basic cobalt salt substrate material coated with dopamine polymer is as follows: cobalt chloride and urea are dissolved in deionized water, and a needle-shaped basic cobalt salt array is grown on a conductive substrate by a chemical bath deposition method to obtain a substrate material with basic cobalt salt grown thereon; The substrate material with the basic cobalt salt grown thereon is soaked in a dopamine solution for a certain period of time, then taken out, its surface is rinsed with deionized water and dried, so that a uniform layer of dopamine polymer is coated on the surface of the basic cobalt salt.
3. The method for preparing a platinum-doped modified cobalt-based catalyst according to claim 2, characterized in that: The concentration of dopamine is 0.1-0.4 mg / L, and the substrate material is immersed in the dopamine hydrochloride buffer solution for 12-24 h.
Citation Information
Patent Citations
Method for preparing carbon hollow sphere composite material with low platinum loading capacity, product and application
CN110690463A
Method for preparing nitrogen-doped carbon nanotube coated cobalt metal electrocatalyst
CN113258080A